Hydrodynamic Calculations of the Movement of Two Phase Systems in Complex Pipelines - Gurbanov, A.N.; Sardarova, I.Z. (Herald of Azerbaijan Engineering Academy, 2024)
Based on hydromechanics of homogenous fluid and gas, a new model of two- phase systems movement of fluid-gas type in horizontal tubes is suggested and the major calculation formula for the complicated development. This method enables us to define the main parameters of the complicated pipelines considering the physical properties of two- phase systems. The equation of two-phase systems movement in simple and complicated pipelines, allowing recommending using this approach in field experience is also obtained.